Towards a thesaurus of plant characteristics: an ecological contribution - Garnier, Eric (2017)
The context of Open Biological Ontologies; (ii) whenever possible, the Entities and Qualities aretaken from existing terminology standards, mainly the Plant Ontology (PO) and Phenotypic QualityOntology (PATO) ontologies; and (iii) whenever a characteristic already has a definition, if appropriate,it is reused and referenced. The development of TOP, which complies with semantic web principles,was carried out through the involvement of experts from both the ecology and the semanticsresearch communities. Regular updates of TOP are planned, based on community feedback andinvolvement.3. TOP provides names, definitions, units, synonyms and related terms for about 850 plant characteristics.TOP is available online (www.top-thesaurus.org), and can be browsed using an alphabeticallist of characteristics, a hierarchical tree of characteristics, a faceted and a free-text search, andthrough an Application Programming Interface.4. Synthesis. Harmonizing definitions of concepts, as proposed by TOP, forms the basis for betterintegration of data across heterogeneous data sets and terminologies, thereby increasing the potentialfor data reuse. It also allows enhanced scientific synthesis. TOP therefore has the potential toimprove research and communication not only within the field of ecology, but also in related fieldswith interest in plant functioning and distribution